(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
Osteoarthritis (OA) is a chronic, degenerative joint disease characterized by progressive cartilage breakdown, subchondral bone changes, osteophyte (bone spur) formation, and joint dysfunction. It is the most common joint disorder, especially in older adults.